Relation between serum sclerostin and CTRP3 levels and bone mineral density in diabetic postmenopausal women - Inass Hassan Ahmad; Sally Said Abd Elhamed Gbr; Basma Mohamed Mohamed Ali El Naggar; Marwa Khairy Abdelwahab; Entesar Omar Ahmad El-saghier; Doaa Sayed Mohammed; Marwa Abdelmonim Mohamed; Maha S. Mohamed; Marwa Mohamed M. Ali Abd El-Rahim; Shahinaz El Attar (BMC, 2024)
Abstract Background Osteoporosis (OP) is a common finding in diabetic patients especially high-risk populations such as postmenopausal women. Sclerostin is a glycoprotein chiefly secreted by mature osteocytes and is considered a main regulator of bone formation. The C1q/TNF-Related Protein 3 (CTRP3) was found to be significantly associated with OP in postmenopausal women. The effect of type 2 diabetes mellitus (T2DM) on sclerostin and CTRP3 levels in postmenopausal women is rarely investigated. The present study aimed to assess the impact of T2DM on sclerostin and CTRP3 levels and their relation to OP in postmenopausal women. Methods The study included 60 postmenopausal women with T2DM and 60 age-matched postmenopausal non-diabetic women. Bone mineral density (BMD) was assessed using dual energy X-ray absorptiometry (DEXA). Serum levels of sclerostin and CTRP3 were assessed using enzyme-linked immunosorbent assay (ELISA) technique. Results Diabetic group expressed significantly higher serum levels of sclerostin when compared with non-diabetic group (110.0 ± 29.0 versus 51.5 ± 23.2 ng; p < 0.001). Oppositely, CTRP3 were significantly lower in the diabetic group (3.5 ± 3.5 versus 9.9 ± 3.7 ng/ml, p < 0.001). Multivariate logistic regression analysis identified HbA1c levels [OR (95% CI): 0.49 (0.26-0.93), p = 0.028], sclerotin levels [OR (95% CI): 1.06 (1.0-1.012), p = 0.041] and CTRP3 levels [OR (95%) CI: 1.64 (1.0-2.68), p = 0.047] as significant predictors of OP in diabetic patients. Conclusions Sclerostin and CTRP3 levels are involved in OP in postmenopausal diabetic patients.